Academic Emotions, Emotion Regulation, Academic Motivation, and Approaches to Learning: A Person-Centered Approach - Christos Rentzios; Evangelia Karagiannopoulou; Georgios Ntritsos (Behavioral Sciences)
Contemporary educational literature suggests that academic emotions and emotion regulation should be explored in tandem, while academic motivation has been discussed both as a self-regulation metacognitive construct and as a construct inherently tied to motivation. The present study uses a person-centered approach to explore profiles of university students based on academic emotions, emotion regulation, academic self-regulation, and approaches to learning. In addition, the impact of students’ profiles on academic performance (GPA) is investigated. The sample consists of 509 university students studying at a Greek university social science department. Cluster techniques and multivariate analysis of variance are used to identify the profiles and test for differences among them. Students were grouped in clusters that revealed both consistent and dissonant patterns of scores on the relevant variables. Analysis reveals three distinct profiles: (a) the “Anxious, effectively-engaged, and organized learners”, (b) the “Deep, Happy, and intrinsically motivated learners” and (c) the “Disengaged, Bored, and Suppressing Learners”. These profiles open new insights into educational literature, revealing links among learning, emotional, and motivational factors. Practical implications and directions for future research are discussed.